EFFECTIVENESS OF THE PROCESS OF CLEANING NATURAL ALFALFA (Medicago sativa L.) AND RED CLOVER (Trifolium pratense L.) SEEDS - Đokić, Dragoslav (Journal on Processing and Energy in Agriculture, 2020)
This paper presents the results of the cleaning tests of three different natural alfalfa seed lots and three different red clover seed lots performed using seed processing machines. The alfalfa (Medicago sativa L.) and the red clover (Trifolium pratense L.) are two of the most important perennial forage legumes in the Republic of Serbia. Alfalfa and red clover seeds for sowing should be clean, i.e. free from weeds and foreign matter, and of high germination and genetic values. Such requirements can only be achieved by cleaning, i.e. removing all undesirable impurities and poor-quality seeds. The following parameters important for the seed cleaning process and equipment were observed: seed purity, contents of weed and other crop seeds, inert substance content, amounts of processed seeds (kg), seed loss and processing output. The results obtained facilitate (depending on the amount and type of weeds and other impurities found in the alfalfa and red clover seed lots considered) the proper adjustment of the seed processing equipment to obtain the largest possible quantity of quality seeds that are in compliance with the laws and regulations of Serbia.
Keywords: alfalfa; red clover; seeds; cleaning; weeds